Separation and recovery of ammonium from industrial wastewater containing methanol using copper hexacyanoferrate (CuHCF) electrodes. (1st January 2021) - Gao, Rui; Bonin, Luiza; Arroyo, Jose María Carvajal; Logan, Bruce E.; Rabaey, Korneel
Highlights: NH4 + in real wastewater containing organics inserts in CuHCF electrode. NH4 + removal of 92.9 ± 0.1 % achieved at + 0.3 V vs. Ag/AgCl. NH4 + regeneration of 88.9 ± 0.4 % achieved at + 1.1 V vs. Ag/AgCl. The stability and durability of CuHCF coated electrodes need to be improved further. Abstract: Ammonium is typically removed from wastewater by converting it to nitrogen gas using microorganisms, precluding its recovery. Copper hexacyanoferrate (CuHCF) is known to reversibly intercalate alkali cations in aqueous electrolytes due to the Prussian Blue crystal structure. We used this property to create a carbon-based intercalation electrode within an electrochemical cell. Depending on the electrode potential, it can recover NH4 + from wastewater via insertion/regeneration while leaving organics. In the first phase, different binders were evaluated towards creating a stable electrode matrix, with sodium carboxymethyl cellulose giving the best performance. Subsequently, based on voltammetry, we determined an intercalation potential for NH4 + removal of + 0.3 V vs. Ag/AgCl, while the regeneration potential of the electrode was + 1.1 V (vs. Ag/AgCl). Using the CuHCF electrodes 95% of the NH4 + in a synthetic wastewater containing 56 mM NH4 + and 68 mM methanol was removed with an energy input of 0.34 ± 0.01 Wh g −1 NH4 + . A similar removal of 93% was obtained using an actual industrial wastewater (56 mM NH4 +, 68 mM methanol, 0.02 mM NO2 −, 0.05 mM NO3 −, 0.04 mM SO4 2− and 0.34 mM ethanol), with an energy input of 0.40 ± 0.01 Wh g −1 NH4 + . In both cases, there was negligible removal of organics. The stability of CuHCF electrodes was evaluated either by open circuit potential monitoring (61 h) or by cyclic voltammetry (50 h, 116 cycles). The stability during cycling of the electrode was determined in both synthetic and real streams for 25 h (125 cycles). The charge density (C cm −1 ) of the CuHCF electrodes declined by 17 % and 19% after 125 cycles in the synthetic stream and the actual wastewater, respectively. This study highlights the possibility of low-cost CuHCF coated electrodes for achieving separation of NH4 + from streams containing methanol. The stability of electrodes has been improved but needs to be further enhanced for large-scale applications and long-term operation. Graphical abstract: Image, graphical abstract